Conditions of existence of univalently stressed contours in the first main problem of the theory of elasticity for a plane with cut - Lozhkin, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
A definition of a univalently stressed contour in a compressible isotropic plane with a curvilinear cut is given, which extends the notion of an equiresistant contour. Conditions for elliptic and square contours to be univalently stressed are formulated and proved.